If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 580 = 29x Reorder the terms: 580 + 20x = 29x Solving 580 + 20x = 29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29x' to each side of the equation. 580 + 20x + -29x = 29x + -29x Combine like terms: 20x + -29x = -9x 580 + -9x = 29x + -29x Combine like terms: 29x + -29x = 0 580 + -9x = 0 Add '-580' to each side of the equation. 580 + -580 + -9x = 0 + -580 Combine like terms: 580 + -580 = 0 0 + -9x = 0 + -580 -9x = 0 + -580 Combine like terms: 0 + -580 = -580 -9x = -580 Divide each side by '-9'. x = 64.44444444 Simplifying x = 64.44444444
| 5(x-2)-4x+8=-7 | | 15+2a=-2 | | 15+2=-2 | | 5-(-3)a=2 | | 7(5-x)=2(7-x) | | 2x-xy=9 | | ln(x+1)+ln(x-1)=ln(15) | | 3(7-x)=2(5+x) | | 11-5a=24 | | 5(4z-1)-4(z+7)=12(z+1) | | 23(x-4)=22(x+4) | | 4x-25=x-5 | | d=14cm | | X^4-27x^2+1=0 | | 15(8x-4)-2x=-8 | | 42(x+1)+42x=13x(x+1) | | 9.6x+15.69=-10.4x+15.53 | | 8x+22=2x+184 | | (-8x)(5x^4)= | | -6(t-6)-(t-6)=11 | | 82-5x=13x+16 | | 9-9x=153-37x | | 4-6x+4x=-1-5(7-2x) | | 126-6x=2x-22 | | 20x^2+20=41x | | -19-2x=17-7x | | .2(2x-6)=3 | | 40-8x=27+3x | | .4(2x-6)=3 | | 7-7x=9+3x | | 2x-5=12x-37 | | x^2+2x^2-9x=18 |